Privacy Enforcement in a Cost-Effective Smart Grid - Mikkelsen, Søren Aagaard (Technical Report Electronics and Computer Engineering, 2014)
In this technical report we present the current state of the research conducted during the first part of the PhD period. The PhD thesis “Privacy Enforcement in a Cost-Effective Smart Grid” focuses on ensuring privacy when generating market for energy service providers that develop web services for the residential domain in the envisaged smart grid. The PhD project is funded and associated to the EU project “Energy Demand Aware Open Services for Smart Grid Intelligent Automation” (SmartHG) and therefore introduces the project on a system-level. Based on this, we present some of the integration, security and privacy challenges that emerge when designing a system architecture and infrastructure. The resulting architecture is a consumer-centric and agent-based design and uses open Internet-based communication protocols for enabling interoperability while being cost-effective. Finally, the PhD report present the envisaged future work and publications that will lead to completion of the PhD study.